HUMOR AND LAUGHTER IN THE PEDAGOGICAL COMMUNICATIONS - Kincāns, Vladimirs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article analyzes the possibilities of humour and laughter in educational activity. Using techniques based on the knowledge of methodological potential of laughter is a substantial reserve for increasing the effectiveness of training, education and personal development. From a pedagogical point of view, means of creating a comic situation is a way of indirect pedagogical interaction with the audience. Laughter helps to observe generally accepted social norms of behaviour, avoid conflicts, defuse the situation, remove emotional tension and enhance the intellectual activity of students.